At the center of the storm - Tenet, George, 1953-; Harlow, Bill.; Conger, Eric. ([S.l.] : HarperAudio, 2007)
An account of the war on terror by a former CIA director traces the author's intelligence career, offers insight into the agency's inner workings, and discusses how America was both prepared and unprepared for the September 11 attacks.
Compact discs.
Abridged.
Read by Eric Conger ; preface and afterword read by the author.
Keywords: Tenet, George, -- 1953-; United States. -- Central Intelligence Agency -- Officials and employees -- Biography; Intelligence officers -- United States -- Biography; Intelligence service -- United States; Audiobooks; United States -- Foreign relations -- 1993-2001.; United States -- Foreign relations -- 2001-2009.